The Holy Roman Empire in conservative political thought - Reho, FO (2024)
This thesis examines the place of the Holy Roman Empire (henceforth ‘Empire’) in conservative political thought from the Enlightenment to European integration. It shows that the Empire remained a key conservative ideal of German and European order into the second part of the 20th century. It traces the formation, development, and influence of five distinct strands of conservative thought on the Empire: cosmopolitan, Romantic, national, Borussian and supranational conservatism. It details how they gradually coalesced into a cosmopolitan-supranational strand on the one hand and a national-imperialist strand on the other. Supranational conservatives cherished the early modern Empire of the Habsburgs as the heart of a European federacy that protected and nurtured national individualities while remaining open to political universality. National conservatives celebrated the medieval Empire of the Hohenstaufen as the archetype of a united and powerful Germany that embraced its role as the continent’s hegemon. The former were influential in early conservative defences of the Empire’s constitution, in mid-19th century plans to build up the German Bund into a multinational Central European federacy and in 20th century Catholic conservative and Christian democratic Europeanism. The latter was central to nationalist plans from the early 19th century, furnished the historical underpinning of Weltpolitik and Mitteleuropa at the turn of the 20th century and inspired the revolutionary conservative Reichsideologie of the interwar period as well as the neo-imperial prefigurations of the various ‘New Rights’ after the Second World War. Mainly an exercise in the transnational history of ideologies over the longue durée, the thesis nuances our understanding of the genesis and development of German conservatism and of the Empire’s influence on it, traditionally seen as a contributing factor to Germany’s Sonderweg, culminating in the Nazi Reich. By outlining a supranational strand of conservatism and distinguishing it from the more nationalist one, which has so far received more attention and seems increasingly dominant in contemporary conservatism, it also helps define more precisely the intellectual boundaries between mainstream conservatism and the radical right.